T5 Complement protein c5a induces prolonged neutrophil dysfunction in a clinically relevant model of human bacteraemia. (15th November 2017) - Wood, AJT; Vassallo, A; Okkenhaug, K; Scott, J; Simpson, J; Summers, C; Chilvers, ER; Conway-Morris, A
Abstract : Introduction: Critically ill patients are highly susceptible to nosocomial infections including ventilator-associated pneumonia. Susceptibility to nosocomial infection is heavily influenced by immune-cell failure; however the mechanisms underpinning this process remain incompletely understood. 1 Previously, we have demonstrated that the complement split product C5a impairs the phagocytosis of zymosan by healthy donor and patient neutrophils. 2 In this study, we investigated the underlying mechanism, duration and preventability of C5a-induced neutrophil dysfunction in a clinically relevant in vitro model. Methods: In a new assay, which permits rapid interrogation of neutrophil functions in whole blood, healthy human or murine blood samples were exposed to C5a or vehicle control, prior to addition of pH-sensitive Staphylococcus aureus bioparticles. Phagocytosis was quantified by flow cytometry with an Attune Next Acoustic Focusing Cytometer (Life Technologies, Paisley, UK). Selective small molecule inhibitors, alternative pro-inflammatory agents, and neutrophils from knock-out mice were used to address our experimental questions. Results: C5a rapidly reduced neutrophil phagocytosis of Staphylococcus aureus in human whole blood by 39.5% (p<0.0001). Moreover, this phagocytic impairment increased over time post-exposure. In contrast to C5a, LPS and platelet activating factor (PAF) increased phagocytosis (p<0.01 and p<0.05 respectively). Prior phagocytosis protected neutrophils from subsequent C5a-induced phagocytic impairment, but this was not recapitulated by exposing neutrophils to soluble priming agents. C5a-induced phagocytic impairment was PI3-kinase dependent in isolated neutrophils, but not in human and murine whole blood. Conclusions: This is the first study to demonstrate the selective ability of C5a to impair neutrophil phagocytosis of a clinically relevant pathogen in a whole blood model which mimics bacteraemia. It also provides intriguing insights into the potential mechanisms by which this may occur, including the temporal dependence of C5a and bacterial exposure. Finally, the ability of PI3-kinase inhibition to ameliorate neutrophil dysfunction may vary depending on whether inhibitors are administered topically or systemically. References: Conway-Morris A, et al . Br J Anaesth 2013;111:778–87. Conway-Morris A, et al . Blood 2011;117:5178–88.